Analysis of the implementation of local wisdom-based learning in the integrated thematic curriculum at MI Pelangi Alam - Susanti, Diah; Putri, Imeilia; Mayasari, Mayasari; Nabila, Siti (The Future of Education Journal, 2025)
This study explores the integration of local wisdom values into thematic curriculum-based learning at MI Pelangi Alam in Ponorogo. The issue addresses how culturally rooted values such as cooperation, humility, and respect are embedded within educational practices to foster character development among elementary students. The research aims to identify effective strategies for implementing local wisdom in teaching, examine its impact on student awareness and character, and explore challenges faced in curriculum integration. Employing a qualitative approach, data were collected through structured interviews, observations, and documentation analysis involving teachers and students. The findings reveal that MI Pelangi Alam successfully incorporates local cultural elements—such as history, culinary traditions, and religious tourism into lessons, which enhances students' understanding of their identity and local resources. The active learning methods, including project-based and cooperative learning, effectively engage students and promote character values aligned with local culture. Support from the community and continuous teacher training further facilitate the integration process. However, challenges such as curriculum constraints and uneven teacher proficiency highlight areas for improvement. Overall, the incorporation of local wisdom values positively influences students' character development and cultural awareness, contributing to the broader goal of forming respectful, confident, and culturally rooted individuals. This research provides insights into sustainable strategies for embedding local culture into primary education.